Quantitative light-induced fluorescence (QLF): A tool for early occlusal dental caries detection and supporting decision making in vivo - Alammari, M.R.; Smith, P.W.; de Josselin de Jong, E.; Higham, S.M. (Journal of dentistry, 2013)
This study reports the development and assessment of a novel method using quantitative light-induced fluorescence (QLF), to determine whether QLF parameters ΔF and ΔQ were appropriate for aiding diagnosis and clinical decision making of early occlusal mineral loss by comparing QLF analysis with actual restorative management. Following ethical approval, 46 subjects attending a dental teaching hospital were enrolled. White light digital (WL) and QLF images/analyses of 46 unrestored posterior teeth with suspected occlusal caries were made after a clinical decision had already been taken to explore fissures operatively. WL and QLF imaging/analysis were repeated after initial cavity preparation. The type of restorative treatment was determined by the supervising clinician independent of any imaging performed. Actual restorative management carried out was recorded as fissure sealant/preventive resin restoration (F/P) or class I occlusal restoration (Rest.) thus reflecting the extent of intervention (=gold standard). All QLF images were analysed independently. The results showed statistically significant differences between the two treatment groups ΔF (p=0.002) (mean 22.60 – F/P and 28.80 – Rest.) and ΔQ (p=0.012) (mean 230.49 – F/P and 348.30 – Rest.). ΔF and ΔQ values may be useful in aiding clinical diagnosis and decision making in relation to the management of early mineral loss and restorative intervention of occlusal caries. QLF has the potential to be a valuable tool for caries diagnosis in clinical practice.